Identification of ellagic acid and urolithins as natural inhibitors of Aβ25–35-induced neurotoxicity and the mechanism predication using network pharmacology analysis and molecular docking - Li, Hui-Lin; Zhang, Shi-Ying; Ren, Ying-Shan; Zhou, Jie-Chun; Zhou, Ying-Xin; Huang, Wei-Zhong; Piao, Xiu-Hong; Yang, Zhi-You; Wang, Shu-Mei; Ge, Yue-Wei (Frontiers in Nutrition, 2022)
Ellagic acid (EA) is a dietary polyphenol that widely exists in grapes, strawberries, and walnuts. It usually exerts multiple biological activities together with its in vivo metabolites called urolithins. EA and urolithins had been proposed as natural agents for applying on the early intervention of Alzheimer’s disease (AD). However, the neuroprotective effects of those small molecules have not been confirmed, and the action mechanism is not clear. Deposition of beta-amyloid (Aβ) protein is well documented as being involved in the initiation and pathological process of AD. In the present study, we investigated the attenuating effects of EA and several urolithins on Aβ25-35-induced neuronal injury and its underlying molecular mechanism by constructing the in vitro AD cell model of PC12 cells and primary neurons. The results revealed that EA and urolithins especially the UM5 and UM6 exerted promising neuroprotective effects in improving the Aβ25-35-induced cell damage and lactate dehydrogenase (LDH) leakage, reducing reactive oxygen species (ROS) production, inhibiting neuronal apoptosis, and promoting neurite outgrowth. These results provide new insights into the development of UM5 and UM6 as anti-AD candidates. A network pharmacology analysis combining molecular docking strategy was further adopted to predict the signaling pathway involved in the anti-AD action of EA and urolithins, and the activation of PI3K-Akt, as well as the inhibition of MAPK was found to be involved.